Persepsi Mahasiswa Program Studi Manajemen terhadap Penerapan Student-Centered Learning dalam Upaya Pelaksanaan Pembelajaran Aktif - Rizky Nastiti; Normalina Normalina (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2022)
This study is focused on analyzing students’ active participation and perceptions of the application of Student-Centered Learning to encourage active learning. This study employed a descriptive method by analyzing the data obtained from the questionnaire. The subjects of this research were students of the Management study program at higher education institutions in Banjarmasin who have been taught using these strategies. The results revealed that the students showed positive perceptions about the strategy used in the classroom. Overall, students considered actively participating in discussions or asking questions to help them understand the material better. When studying in groups, the students could discuss the material given together and share their ideas. The students also believed that participating in discussions and case studies gave them the opportunity to learn more about the real world. The students also stated that they learned to be open-minded and accept reasonable criticism through class debate. In addition, as claimed by students, other benefits of implementing Student-Centered Learning included building interactions between lecturers and students, as well as improving oral communication, critical thinking, and teamwork skills.